Initial experience with a novel resection and plication (RAP) method for acid reflux: a pilot study - Benias, Petros C.; D’Souza, Lionel; Lan, Gloria; Gluckman, Craig; Inamdar, Sumant; Trindade, Arvind J.; Miller, Larry S.; Carr-Locke, David L. (Endoscopy International Open, 2018)
Background and study aims Current endoscopic therapies for gastroesophageal reflux disorder (GERD) are limited by technical complexity, and/or cost. We sought to evaluate the success of a novel resection and plication (RAP) anti-reflux procedure.Patients and methods RAP was performed on 10 patients with GERD refractory to proton pump inhibitor (PPI) therapy. RAP consists of semi-circumferential mucosectomy along with full-thickness plication of the lower esophageal sphincter (LES) and cardia. We assessed the technical success and safety as well as followed GERD-Health Related Quality of Life (GERD-HRQL) scores and medication usage. Results All patients underwent RAP without adverse events and were discharged on the same day. Only half of the patients required general anesthesia. Follow-up ranged from 5 to 24 months (median 9 months) and all patients had a significant improvement in their GERD-HRQL scores (P < 0.0001, 95 % CI 19.3 – 25.3). 8 of 10 eliminated their daily PPI dependence. Conclusions The RAP method has potential as an effective anti-reflux option. Its main advantages include a short procedure time, simple approach using readily available equipment, and possible avoidance of general anesthesia.